Work Environment and Work Productivity of Elementary School Teachers at COVID-19 Pandemic - Muizu, Wa Ode Zusnita; Soemaryani, Imas; Triski, Dara Sagita (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2023)
The Indonesian government implemented an online work environment in aneducational institution to prevent the spread of COVID-19, particularly by suspendingschool/university activities, School organizations’ productivity is strongly influenced by the productivity of teachers’ work. The long process of implementing online learning during the pandemic may have impacted the teachers at Integrated Islamic Elementary Schools in terms of productivity. In the 2020 academic year, there was a decline in teacher work productivity of 70-75%, as measured by the effectiveness and efficiency of teachers’ abilities. The purpose of this study was to determine the impact of the work environment on teacher productivity. A total of 138 people were included in this study. Surveys, interviews, and questionnaires are all used to collect data. Meanwhile, data processing and analysis were performed using a simple linear regression method. According to the coefficient of determination test, the R-square is 0.65, indicating that changes in the teacher’s work environment have a 65% effect on the teacher’s work productivity, with the rest influenced by other variables. The results of the research are the work environment has a positive effect on teacher work productivity.